The effect of physician-nurse substitution in primary care in chronic diseases: a systematic review (Swiss Medical Weekly, 2015)
BACKGROUND: Chronically ill and ageing populations demand increasing human resources who can provide on-going and frequent follow-up care. We performed a systematic review to assess the effect of physician-nurse substitution on process care outcomes. METHODS: We searched OVID Medline, Embase, CINAHL and The Cochrane Library for all available dates up to August 2012 and updated in February 2014. We selected and critically appraised published randomised controlled trials (RCT) and followed the PRISMA guidelines for the reporting of systematic reviews. RESULTS: A total of 14 RCTs comprising 10,743 participants met the inclusion criteria. Studies were generally small and suffered from attrition of ≥20% and selection biases. There were 53 process measurements investigated in the 14 RCTs, many of which were unique to specific conditions. Accounts of nurses’ roles, responsibilities, tasks, qualifications and training content/components were not described in sufficient detail. Most study estimates showed no significant differences between nurse-led care and physician-led care while less than a half (~40%) favoured nurse-led care. CONCLUSIONS: Despite the methodological limitations and the varying nurses’ roles and competencies across studies, specially trained nurses can provide care that is at least as equivalent to care provided by physicians for the management of chronic diseases, in terms of process of care. Future, larger studies with better quality methods are needed and should report and assess whether the differences in effects vary due to diversity in roles, qualifications, training competencies and characteristics of clinicians delivering substitution of care.